Prior chronic clopidogrel therapy is associated with increased adverse events and early stent thrombosis - Asher, Elad; Fefer, Paul; Sabbag, Avi; Herscovici, Romana; Regev, Ehud; Mazin, Israel; Shlomo, Nir; Zahger, Doron; Atar, Shaul; Hammerman, Haim; Polak, Arthur; Beigel, Roy; Matetzky, Shlomi; for The PLATIS (Platelets and Thrombosis in Sheba) Study Group (Thrombosis and Haemostasis, 2016)
Despite the growing use of clopidogrel, limited data exist regarding the prognostic significance of chronic clopidogrel therapy in patients sustaining acute coronary syndrome (ACS). Our aim was to determine whether patients sustaining ACS while on chronic clopidogrel therapy have a worse prognosis than clopidogrel-naïve patients. A total of 5,386 consecutive ACS patients were prospectively characterised and followed-up for 30 days. Of them, 680 (13 %) were treated with clopidogrel prior to the index ACS. Major adverse cardiovascular events (MACE) were defined as death, recurrent ACS, stroke and/or stent thrombosis. Compared with clopidogrel-naïve, chronic clopidogrel-treated patients were older (66 ± 12 vs 63 ± 13, respectively; p< 0.01), suffered more from diabetes mellitus, hypertension, dyslipidaemia, prior cardiovascular history, including prior myocardial infarction, revascularisation, coronary artery bypass graft and stroke (p< 0.01 for all), and were less likely to present with ST-elevation myocardial infarction (21 % vs 45 %; respectively; p < 0.001). Prior clopidogrel therapy was associated with a two-fold increase in in-hospital (1.6 °% vs 0.6, respectively; p =0.006) as well as 30-day stent thrombosis (2.2 % vs 1.0 %, respectively; p=0.007). MACE at 30 days was also higher among chronic clopidogrel-treated compared with clopidogrel-naïve patients [12.3 % vs 9.4 %, respectively; p< 0.01]. In multivariate log regression analysis chronic clopidogrel treatment was an independent predictor of stent thrombosis [OR=2.6 (95 %CI 1.2–5.6), p=0.001]. Patients sustaining ACS while on chronic clopidogrel treatment are at higher risk for in-hospital and 30-day adverse outcomes, including stent thrombosis.
Keywords: Chronic clopidogrel therapy; ACS; stent thrombosis